Taxonomical changes and comments on Palaearctic and Oriental Chrysomelidae (Coleoptera) - J. Bezděk (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
Based on the study of primary type material, the following taxonomic changes in Palaearctic and Oriental Galerucinae and Cryptocephalinae (Clytrini) are proposed: Apophylia Thomson, 1858 = Apophylana Medvedev, 2019, syn. n.; Galeruca subgenus Rhabdotilla Jacobson, 1911, stat. n. = Galemira Beenen, 2003, syn. n.; Aulacophora coffeae (Hornstedt, 1788) = Hoplasoma kelantana Medvedev, 2019, syn. n.; Cassena collaris collaris (Baly, 1879) = Cneorane malayana Medvedev, 2019, syn. n.; Coeligetes submetallica Jacoby, 1884 = Doryidella marginata Medvedev, 2015, syn. n.; Dercetina bicolora (Medvedev, 2018), comb. n. (from Doryidella); Dercetina bisbipunctata (Medvedev, 2018), comb. n. (from Doryidella); Galeruca (Rhabdotilla) sexcostata Jacoby, 1904 = Rhabdotilla rosti Jacobson, 1911, syn. n.; Menippus beeneni Lee, Bezděk et Suenaga, 2012 = Pyrrhalta shaanxiana Medvedev, 2019, syn. n.; Pseudocneorane apicalis (Jacoby, 1884), comb. n. (from Metrioidea) = P. fulvicornis Medvedev et Romantsov, 2012, syn. n.; Pseudocneorane grandis (Allard, 1889), comb. n. (from Metrioidea); Pseudocneorane molek (Mohamedsaid, 1994), comb. n. (from Metrioidea); Radymna rickmersi (Weise, 1900) = Galeruca (Haptoscelis) reitteri Havelka, 1958, syn. n. Galerucella flavidula Reitter, 1913, syn. n. is removed from the synonymy with G. tenella (Linnaeus, 1760) and newly synonymized with G. pusilla (Duftschmid, 1825). Following new names are proposed due to homonymy: Smaragdina vitalisi nom. n. for S. divisoides Medvedev, 1988, nec Gynandrophthalma divisoides Chûjô, 1952 (now junior synonym of Smaragdina fulveola (Jacoby, 1890)); Smaragdina gerhardi nom. n. for S. schereri Lopatin, 2006, nec S. schereri Medvedev, 1970 (now Afrophthalma schereri); Apophylia skalei nom. n. for A. thoracica (Medvedev, 2019), nec A. thoracica Gressitt et Kimoto, 1963 (junior synonym of A. flavovirens (Fairmaire, 1878)); Monolepta hagiangana nom. n. for M. bacboensis Medvedev, 2015, nec M. bacboensis Medvedev, 2012. The spelling of Smaragdina cribripennis Tan, 1988 is fixed in accordance with the principle of the First Reviser.